Mortality in critical illness: The impact of asymmetric dimethylarginine on survival—A systematic review and meta‐analysis. Issue 6 (14th March 2019) - Mortensen, Karoline Myglegård; Itenov, Theis Skovsgaard; Hansen, Marco Bo; Hvid, Karen; Lundstrøm, Lars Hyldborg; Bestle, Morten Heiberg
Abstract : Introduction: Asymmetric dimethylarginine (ADMA), an endogenous inhibitor of the nitric oxide system, may be associated with an adverse outcome in critically ill patients. The aim of the present review was to clarify if plasma ADMA and the arginine‐to‐ADMA ratio (arginine/ADMA) are associated with mortality in critically ill patients. Methods: We searched PubMed, EMBASE and Web of Science/BIOSIS Previews on 31 July 2017 for studies published after 2000 including critically ill paediatric or adult patients and evaluating any association between all‐cause mortality and admission ADMA and/or arginine/ADMA ratio. We pooled data from studies providing sufficient data in random effects meta‐analyses. Results: We identified 15 studies including a total of 1300 patients. These studies have a medium to high risk of bias and substantial clinical heterogeneity. After contacting authors for homogenous data, six studies including 705 patients could be included in a formal meta‐analysis. This analysis revealed a strong association between high plasma ADMA upon admission and mortality (pooled odds ratio 3.13; 95% confidence interval (CI) 1.78‐5.51). A significant association between ADMA/arginine ratio and mortality was found in two studies only (54 patients) out of a total of six studies (564 patients). Conclusions: A high plasma ADMA level upon admission is strongly associated with mortality in critically ill patients. However, there is no association between the arginine/ADMA ratio and mortality in this group of patients. The pathophysiological role of ADMA in circulatory collapse and its potential as a target for intervention remains to be explored.